Retour d’expérience sur le développement participatif d’un jeu sérieux à destination des professionnels de l’acte de construire et d’aménager - Fanny Coulombié; Véronique Dufour (Netcom)
Ville & Aménagement Durable developed the serious game called VADemecum in order to strengthen the interchanges between the various stakeholders involved in spatial development and urban planning. In this role-playing game, participants design and develop a project in a collaborative way. VADemecum serious game can be employed in several contexts : professional workshops, continuous or in-company trainings to advance transversality, at the earliest stages or before the beginning of real projects or as a tool for citizen consultations. First games of this iterative and reflexive process brought to light the facilitator’s major role for smooth and successful games. It also revealed the importance of a game board and indicators choices in order to ensure a good cooperation and immersion. Eventually, these first games led us to change in a significant way the balance between maximum likelihood and pedagogy.